A Probe Into The Comparison Of Human Translation And DeepL Translate In Translating English Text Into Indonesian: English - Rika Vennita; Yenni Hasnah (Journal of English Development, 2024)
This research aims to analyze the difference between human translation and deep translation in translating English text into Indonesian. This research describes the accuracy, acceptability and readability of the results of human translation and translation tools. This research is a type of qualitative research, and the data source of this research is a short story text. The study involved two students of different genders enrolled in the English education program at Universitas Muhammadiyah Sumatera Utara. The researcher used the text document as an instrument tool, and the researcher will collect the results and descriptive data obtained from 4 stages: data collection, data reduction, data presentation, and conclusion drawing. The data reveals that women had an accuracy rate of 88%, while males achieved a rate of 56%. The acceptance level for language or words was 92% for females and 75% for males. The readability level achieved was 92% for females and 72% for males. Additionally, the researcher examined the degree of accuracy 88%, acceptability 88%, and readability 100% from the standpoint of DeepL Translate. From these results, we can conclude that the selection of translation tools is essential to help the translation process carried out by humans.